Plan de ordenamiento turístico para el desarrollo de las parroquias rurales Boyacá y Eloy Alfaro del Cantón Chone - Castillo Loor, Jorge Adrián (2024)
The objective of this investigative work was to design a tourism planning plan for the development of the Boyacá and Eloy Alfaro parishes in Chone canton. It was structured with four phases: the first carried out the situational diagnosis of both parishes, characterizing and delimiting the study area, to assess existing tourist potential; with the help of the matrix of those involved, the main territorial actors were identified; multidimensional matrices were also applied that allowed us to know the current state of the parishes, resulting in the Eloy Alfaro parish having more tourism potential than the Boyacá parish. The second phase, identification of tourist products with territorial identity linked to the agricultural, agro-industrial, gastronomic, artisanal, natural and cultural fields. Altogether, 100 surveys were applied per parish, revealing that both have agroindustrial potential, due to the production of cheese and products made from milk. In the third phase, a SWOT matrix was developed that allowed us to know the strengths, opportunities, weaknesses and threats that these parishes have; to prepare this, the information obtained through a multidimensional matrix and field trips was taken as a reference, resulting in the fact that both can develop agroindustrial activities to link tourism. The fourth phase was a tourism planning plan in which it is proposed to study tourist zoning, using tools such as ArcGIS, to locate spaces with greater potential. Finally, programs and projects are proposed aimed at improving the quality of life of the territorial population, concluding that both parishes could be based on agroindustrial/agricultural activities to project themselves as tourists.